Phylogenetic relationship of WRKY transcription factors in Solanum and potato genes in response to hormonal and biotic stresses - Dequan Jiang; Wenjuan Huang; Jia Liu (Plant Signaling & Behavior)
WRKY transcription factors are important regulators of plant responses to environmental stresses and hormone signaling. This study analyzes the WRKY gene family in Solanum tuberosum by examining the phylogenetic relationships, expression profiles, and their roles in abiotic stress and hormone responses. Phylogenetic tree was constructed using 322 WRKY genes from four Solanum species: S. tuberosum, S. pennellii, S. pimpinellifolium, and S. lycopersicum. The results revealed conserved and expanded WRKY genes across these species. We then studied the expression of 75 SotuWRKY genes in response to salt, drought, heat stresses, and hormone treatments (IAA, ABA, BABA, GA3, and BAP). Results showed that 19, 25, and 29 genes were regulated under salt, drought, and heat stresses, respectively. Several WRKY genes (e.g. SotuWRKY03 and SotuWRKY24) were also regulated by biotic stresses like Phytophthora infestans infection and hormone treatments, indicating their involvement in plant defense mechanisms. A gene co-expression network was constructed based on gene-to-gene correlations, where SotuWRKY52 was identified as a hub gene, positively regulating six WRKY genes and negatively regulating four. These findings suggest that potato WRKY genes play key roles in regulating stress responses and hormone signaling, potentially enhancing potato resistance to stresses and diseases. This study provides new insights into WRKY transcription factors in S. tuberosum and other Solanum species.